Mengapa Tetap Bertahan? Pengalaman Istri Narapidana Mempertahankan Pernikahan - Rizda Yuli Sukmawati; Vania Ardelia (Universitas Al Azhar Indonesia, 2026)
This study aims to understand the experiences of prisoners' wives in maintaining marital bonds amidst the imprisonment of their spouses. The study used a qualitative approach with a phenomenological design. Data were collected through in-depth interviews with 10 prisoners' wives, then analyzed using thematic analysis techniques. The research findings indicate that wives' decisions to maintain their marriages are influenced by a number of psychological factors, including responsibility for children, emotional attachment, moral values, and an assessment of the balance between sacrifice and emotional benefits in the relationship. The physical absence of the husband during imprisonment makes the wife a primary factor in maintaining family stability while meeting the emotional needs of the children. The results confirm that marital continuity does not reflect a passive attitude, but rather a psychological strategy shaped by emotional regulation, social support, and humanitarian values. These findings are expected to contribute to the development of psychosocial interventions to strengthen family resilience in the context of imprisonment.Keywords – Convict’s wife, Imprisonment, Marital Resilience, Phenomenology.